2021
DOI: 10.1038/s41598-021-81880-7
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of chitosan from Ugandan edible mushrooms, Nile perch scales and banana weevils for biomedical applications

Abstract: Of recent, immense attention has been given to chitosan in the biomedical field due to its valuable biochemical and physiological properties. Traditionally, the chief source of chitosan is chitin from crab and shrimp shells. Chitin is also an important component of fish scales, insects and fungal cell walls. Thus, the aim of this study was to isolate and characterize chitosan from locally available material for potential use in the biomedical field. Chitosan ash and nitrogen contents ranged from 1.55 to 3.5% a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 77 publications
3
19
2
Order By: Relevance
“…The C-O stretching vibrations peaks from ~1061 and ~1021 cm −1 and the N-H wag (for the primary and secondary amines) from ~893 cm −1 were specific for the polysaccharide structure of the chitosan. The characteristic bands/peaks of the chitosan FTIR spectrum found in this study were comparable with the values reported by other researchers [ 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Resultssupporting
confidence: 91%
“…The C-O stretching vibrations peaks from ~1061 and ~1021 cm −1 and the N-H wag (for the primary and secondary amines) from ~893 cm −1 were specific for the polysaccharide structure of the chitosan. The characteristic bands/peaks of the chitosan FTIR spectrum found in this study were comparable with the values reported by other researchers [ 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Resultssupporting
confidence: 91%
“…They can be also obtained by synthesis [ 145 ]. The extraction of chitin from the shell includes mainly demineralization and deproteinization [ 185 , 186 , 187 ]. Demineralization is carried out using concentrated hydrochloric acid (HCl) to precipitate the calcium chloride salt.…”
Section: Isolation Of High-value Molecules With Neuroprotective Effects Against Alzheimer’s Diseasementioning
confidence: 99%
“…Thus, ash content of Chitosan-CGNA and commercial chitosan were determined in this study. It is important to mention that the level of demineralization and deproteination determines the purity of chitosan, which affects its biological properties such as immunogenicity, biocompatibility and biodegradability [ 30 ]. According to Ssekatawa et al [ 30 ], chitosan with an ash content lower than 1% possesses superior biological properties and is recommended for biomedical applications.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to mention that the level of demineralization and deproteination determines the purity of chitosan, which affects its biological properties such as immunogenicity, biocompatibility and biodegradability [ 30 ]. According to Ssekatawa et al [ 30 ], chitosan with an ash content lower than 1% possesses superior biological properties and is recommended for biomedical applications. The chitosan obtained in this study presented an ash content of 0.11% and this value is fit for medical applications.…”
Section: Resultsmentioning
confidence: 99%